2021
DOI: 10.3389/fgene.2021.563623
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Long Noncoding RNAs and mRNAs in Granulosa Cells of Jinghai Yellow Chickens Illuminated With Red Light

Abstract: Jinghai Yellow chickens are a new indigenous breed with a dual purpose in China, but their egg laying performance is limited. Compared with white light (WL), exposure to red light (RL) can improve the egg laying performance of hens. Herein, to elucidate the molecular mechanism by which RL affects the egg laying performance, RNA sequencing was used to analyze long noncoding RNAs (lncRNAs) and mRNAs from granulosa cells of small yellow follicles from Jinghai Yellow chickens in RL and WL groups. A total of 12,466… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Moreover, RNA sequencing was used to analyze mRNAs and long noncoding RNAs (lncRNAs) from granulosa cells of SYFs from Jinghai Yellow chickens in exposure to red light and white light groups. One thousand one hundred eighty-two DEGs were identified and the integrated network analysis shown that several of them were involved in follicular development through steroid hormone synthesis, oocyte meiosis, and the PI3K-Akt signaling pathway [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, RNA sequencing was used to analyze mRNAs and long noncoding RNAs (lncRNAs) from granulosa cells of SYFs from Jinghai Yellow chickens in exposure to red light and white light groups. One thousand one hundred eighty-two DEGs were identified and the integrated network analysis shown that several of them were involved in follicular development through steroid hormone synthesis, oocyte meiosis, and the PI3K-Akt signaling pathway [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous lncRNA studies have been performed in the chicken, and adipogenesis-associated lncRNAs have been identified, , functional study on lncRNAs has been less explored. In the current study, we identified that a conserved lncPRDM16 in the abdominal adipose tissue in chickens could inhibit preadipocyte proliferation due to the functional importance of 250 nucleotides at 5′-end, which potentially regulate the transcriptional activity of both promoters of lncPRDM16 and PRDM16.…”
Section: Discussionmentioning
confidence: 99%
“…In the chicken, numerous lncRNA studies have been performed recently on its relationship with chicken growth and diseases. lncRNAs associated with adipose tissue growth and development, or preadipocyte differentiation, were also identified. , Tissue-specific lncRNAs (liver and adipose tissues) were cataloged first and a large number of lncRNAs during abdominal and intramuscular preadipocyte differentiation were then enlisted. , Recently, a comprehensive transcriptome sequencing study on intramuscular and abdominal fat tissues identified an important lncRNA, lncAD, and another study found a novel lncRNA (IRLnc) related to intramuscular fat deposition . However, detailed functional investigation of the molecular function of these lncRNAs remains less explored.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have identi ed an important role for lncRNAs in the regulation of follicle development (19,20). Studies have identi ed differential expression of lncRNAs associated with reproductive function by using RNA-seq of OGCs obtained from humans (21), pigs (22), and chickens (23). Most of those studies have focused on PCOS (24,25), endometriosis (26, 27), and POF (28, 29).…”
Section: Discussionmentioning
confidence: 99%